Blended learning strategies through guided inquiry learning settings to increase learning acquisition of concepts and procedures in biology subjects - Lilan Dama; Nurrijal Nurrijal (Biosfer: Jurnal Pendidikan Biologi, 2023)
The application of blended learning strategies through guided inquiry learning arrangements aims to increase the acquisition of students' learning concepts and procedures on the material of the body's defense system. The purpose of this study was to examine the effect of blended learning strategies with guided inquiry learning settings on the acquisition of learning concepts and procedures in biology subjects in high school. This test was carried out using a pre-experimental one group pre-test and post-test design, in this design:a) measurement of dependent variables from one group of subjects (pretest), b) subjects were given treatment for a certain period of time (exposure). , c) the second measurement (posttest) was carried out on the independent variables, and d) comparison of the results of pretest and posttest measurements. This study involved 36 students of second grade of Science class 3 of Public Senior High School 3 Gorontalo, consisting of 22 women and 14 men. The results of this study are; (1) Provide scientific experience so that it can become the best practice for fostering student teacher candidates. (2) Contribute directly to schools through teacher partnerships in finding the right learning mode. (3) The blended learning strategy of guided inquiry learning settings is very good in giving effect to increase the acquisition of learning concepts and procedures of students on the material of the body's defense system in Biology subjects in high school.